Delineating the Subarachnoid Space in the Adult Lumbosacral Spine Using Computed Tomographic Myelography: An Aid for Clinical Target Volume Delineation in Craniospinal Irradiation - John S. Peterson, BA; Miriam E. Peckham, MD; Matthew M. Poppe, MD; Lindsay S. Burt, MD; Dennis C. Shrieve, MD, PhD; Donald M. Cannon, MD (Advances in Radiation Oncology, 2022)
Purpose: Our aim was to characterize the patterns of cerebrospinal fluid (CSF) extension in the lumbosacral spine using computed tomography (CT) myelograms to provide an evidence base for clinical target volume (CTV) definition in adults receiving craniospinal irradiation. Methods and Materials: This was a retrospective analysis of diagnostic CT lumbar myelograms performed in 30 patients between the ages of 22 and 50. Lateral extension of CSF beyond the thecal sac was measured along each lumbar and sacral nerve root to the nearest millimeter, as was the distance of inferior extension of CSF beyond the caudal end of the thecal sac. Each patient's lateral and inferior CSF extensions were mapped onto a standardized CT data set to create a model target volume in the lumbosacral spine that would contain the aggregate observed CSF distributions from the analyzed CT myelograms. The median extension distances, interquartile ranges, and 90th percentile for distance at each level were calculated. Results: The median lateral extension of CSF along nerve roots beyond the thecal sac—as measured perpendicular to the longitudinal axis—increased from 0 mm (interquartile range [IQR], 0-4 mm) at L1 to 8 mm (IQR, 6-12 mm) at S1 and 0 mm (IQR, 0-0 mm) at S4. The 90th percentile ranged from 5 to 14 mm laterally, with a pattern partially extending into the S1 and S2 sacral foramen. Median CSF extension inferior to the caudal sac was 5 mm (IQR, 2-8 mm), with 90% of patients within 12 mm. An atlas was generated to guide CTV delineation for highly conformal radiation techniques. Conclusion: These results provide information on patterns of CSF extension in the lumbosacral spine of adults and can serve as a model for CTV guidelines that balance comprehensive coverage of the CSF compartment while minimizing the dose to nontarget tissues.